Development and Validation of VM-PATHI: Vestibular Migraine Patient Assessment Tool and Handicap Inventory. Issue 4 (April 2020) - Sharon, Jeffrey D.; Krauter, Roseanne; Kirk, Laura; Pasquesi, Lauren; Allen, Isabel E.; Formeister, Eric J.; Michael, Rebecca L.; Levin, Morris
Abstract : Objective: The aim of this article is to develop and validate a disease-specific, patient-reported outcome measure for vestibular migraine. Setting: Tertiary care vestibular center. Patients: Adult patients with definite or probable vestibular migraine per Barany Society Criteria. Study Design: This was a prospective cohort study. VM-PATHI (Vestibular Migraine Patient Assessment Tool and Handicap Inventory) was developed with expert input, literature review, and patient feedback. VM-PATHI scores were compared between those with vestibular migraine and controls, across several time points, and to other dizziness and quality of life (QoL) measures. Results: A 25-item questionnaire was developed. Cronbach's α was high at 0.92. Test–retest reliability was excellent ( r = 0.90, p < 0.001). Scores were much higher in patients with vestibular migraine (mean 42.5, SD = 16.1) than control patients (mean = 9.6, SD = 8.5). VM-PATHI scores were responsive to treatment ( p = 0.01). Scores were well correlated with general QoL, depression, and anxiety scores. Scores were also correlated with the Dizziness Handicap Inventory ( r = 0.69). An exploratory factor analysis was performed, which revealed 6 distinct factors that corresponded well to different aspects of disease-related symptomatology. Conclusion: VM-PATHI is a valid, reliable, and responsive measure of disease severity in vestibular migraine.